Pengaruh Konsentrasi Graphene Nanosheets Dan Foam Agent Terhadap Kuat Tekan Bata Ringan Cellular Lightweight Concrete (CLC) - Eva Rantika; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Cellular lightweight concrete (CLC) is a material obtained by inserting air bubbles into the lightweight concrete mixture, where the air granules are able to maintain the bubble structure during the curing process. The use of lightweight concretes may reduce the construction costs and make the working process becomes easier. This study aims to make CLC with the addition of graphene nanosheets as an additive to improve the compressive strength and thermal resistance of CLC. This research begain by making the graphene, preparing the sand as fine aggregate, foaming agent, cement, and distilled water then ended with making the light concretes by adding grapheme (1%, 3% and 5%) with the ratio of the foaming agent: water of (1:20, 1:30, 1:40). The morphological results showed an increase in the cavity that was formed with the addition of the foaming agent : water. The results obtained at 5% graphene concentration in the ratio of the foaming agent : water (1:30) were for compressive strength of 2.5 MPa at a density of 1196 grams with the results of porosity and water absorption of 10.431% and 9.119%. The thermal resistance test at 700 ° C reached a compressive strength of 0.5 Mpa.Keywords : Additive, CLC (Cellular Lightweight Concrete), Foaming Agent, Graphene